Platelet Mitochondrial Complex I and I+III Activities Do Not Correlate with Cerebral Mitochondrial Oxidative Metabolism - Powers, William J; Haas, Richard H; Le, Thuy; Videen, Tom O; Markham, Joanne; Perlmutter, Joel S (Journal of cerebral blood flow and metabolism, 2011)
Assays of mitochondrial electron transport system (ETS) activity in circulating blood platelets have been used to investigate the cause of neurodegenerative diseases. However, the correspondence between platelet ETS function and cerebral mitochondrial metabolism is not well characterized. To assess the validity of using platelet ETS activity to infer cerebral mitochondrial metabolism, we measured platelet ETS activity (complex I and complex I+III), cerebral metabolic rate of oxygen (CMRO2), and the CMRO2/cerebral metabolic rate for glucose ratio in 40 subjects: 7 with never-medicated Parkinson's disease, 13 with genetically proved Huntington's disease, and 20 normal controls. We found no correlation between in vivo measures of cerebral mitochondrial oxidative metabolism and ex vivo assays of platelet complex I and complex I+III activity performed on blood collected immediately before cerebral metabolism studies. We saw no evidence of a threshold effect when comparing platelet complex I and complex I+III activity with cerebral oxidative metabolism across a 4- to 10-fold range of platelet ETS activity. On the basis of these data, we conclude that measures of mitochondrial complex I and I+III activity in platelets within the ranges we have studied do not correlate with oxidative function of cerebral mitochondria.